Development of fair play in the world championships last three handball and its relationship to cancel the penalty of expulsion in international law amendments in 2010 - Muhsin, Saad; Muhsin, Saad (Journal of Physical Education, 2023)
The research problem focused in two questions, first: are the IHF successful through its continuous amendments to the rules of the game to reduce Fouls and Unsportsmanlike in the last three Handball World Championship 2005, 2007, 2009? Second: was the decision of the IHF to cancel the penalty of exclusion in 2010 amendment is right?The research sample is twenty-four teams participate in the three tournaments. As show through tables and statistics that the rate of fair play in the continuous improvement from tournament to another, as illustrated in the three tournaments in a row that in one game the rates of warning are (6 –